Research Progress on Preparation and Functions of Alginate Oligosaccharides with Different Structures - HUANG Youtao, LIANG Qingping, GAO Xiaoya, LI Dongyu, MOU Haijin (Shipin Kexue, 2024)
Alginate is one of the most abundant marine polysaccharides, which can be degraded into alginate oligosaccharides (AOS) by chemical, physical and biological methods. AOS, linear oligosaccharide composed of guluronic acid and mannuronic acid, have a variety of biological activities such as antimicrobial, anti-inflammatory, and immunoregulatory activities, and these biological activities are closely related to their structural diversity. AOS prepared by different degradation methods have different uronic acid compositions, polymerization degrees and special structures. Therefore, exploring the structure-function relationship of AOS will help to fully understand the activity of AOS and improve its application value. In this paper, the reaction mechanisms of the various methods to prepare AOS, the structures of the resulting products, and the structure-function relationship of AOS are reviewed in order to provide a reference for further research and application of AOS.